Pengaruh Temperatur Terhadap Kinetika Reaksi Pembentukan Hidroksiapatit (HAp) Dari Precipitated Calcium Carbonate (PCC) Cangkang Telur Itik Melalui Proses Presipitasi - Hadrian Yonas Sebastian Napitupulu; Yelmida Azis; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Hydroxyapatite (Ca10(PO4)6(OH)2) is a calcium phosphate compound that has been widely used as a bone implant material due to its chemical composition is identical with natural bone. The aim of this research is to synthesized, characterized and studied the kinetics of hydroxyapatite synthesis reaction using PCC (Precipitated Calcium Carbonate) of duck egg shell by precipitation method. In this research the samples were taken every 10 minutes as much as 10 mL for 1 hour to determined the reaction kinetic. Then stirred for 24 hours with temperature variation (300C, 400C; 500C; 600C) and aged for 24 hours. The analysis of Ca concentration in filtrate was detected by using complexometri method. The synthesized hydroxyapatite was characterized by XRD and obtained a hexagonal crystalline structure with crystal size between 20 - 37 nm. The reactions kinetics of synthesized hydroxyapatite follows the pseudo first order equation with the value of reaction rate constant (k) is 0,0543 min-1; 0.0759 minutes-1; 0.1146 minutes-1; and 0.1597 minutes-1.Keywords: hydroxyapatite, reaction kinetics, PCC, duck egg shell, precipitation